Pengaruh penggunaan media powerpoint interaktif terhadap motivasi belajar Matematika pada siswa kelas III SD Negeri Sumber Jaya - Clara Anggun Mellenia; Trisniawati Trisniawati; Mahmudah Titi Muanifah; Nelly Rhosyida (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
The aims of this study are: (1) To examine the extent to which students' motivation to learn mathematics is in third grade at SDN Sumber Jaya. (2) To test the extent to which mathematics learning uses interactive PowerPoint media for third-grade students of SDN Sumber Jaya. This type of research is experimental research. The research design used is a Quasi-Experimental Design with the form of a Nonequivalent Control Group. The research subjects were 88 students, which were divided into 3 classes, namely class IIIA with 30 students (experimental class), class IIIB with 30 students (control class), and class IIIC with 28 students (test questionnaire). Data collection techniques used were observation and questionnaires for learning motivation data. The results of the student learning motivation questionnaire were analyzed using a t-test or Independent Samples T-Test, which previously had known normality and homogeneity. In the experimental class, the pre-test average of learning motivation for the experimental class was 93.37 and the control class was 95.07. For the post-test average of the experimental class's learning motivation was 111.39 and the control class was 106.05. In the pre-test normality test, the experimental class's learning motivation was 0.115 and the post-test of the experimental class's learning motivation was 0.114. It can be seen from the significance level of Shapiro-Wilk is more than 0.05, which indicates that the pre-test and post-test data on the learning motivation of the experimental class are normally distributed. Meanwhile, the pre-test of learning motivation for the control class was 0.020 and the post-test for the motivation for learning for the control class was 0.100. It is normally distributed because the significant value on the Shapiro-Wilk is more than 0.05. The results of the homogeneity test of learning motivation with a significant value of 0.75 which means that it is greater than 0.05. It can be concluded that the pre-test and post-test data on the learning motivation of the experimental class and the control class have the same variance. The results of the learning motivation hypothesis test or t-test showed that the significant value was 0.000 <0.05. Based on the results of hypothesis testing, it can be concluded that the use of interactive PowerPoint media affects the motivation to learn mathematics in third-grade students of SD Negeri Sumber Jaya.